Factors Associated with Community Visits to Integrated Non-Communicable Diseases Development Posts (Posbindu PTM) - Nur’Ilmi, Aulia; Manglapy, Yusthin Meriantti; Iftita, Magumi Avrora; Askar, Muhammad Afiq (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Non-communicable diseases are encountered quite often in productive age. Early detection efforts through Posbindu-PTM must be optimized, considering many people still need to gain awareness. What factors play a role in POSBINDU PTM visits in the Tambakharjo is unknown.Method: This research is an observational study with a cross-sectional approach. Systematic sampling was used for 158 people from Tambakharjo aged ≥15 years. Sociodemographic data, history of non-communicable diseases, hypertension knowledge, and POSBINDU PTM visits were collected by interview during November 2023.Result: The research results showed that 22.2% of respondents visited Posbindu-PTM. The multiple logistic regression test showed that the factors that contributed to 99% of POSBINDU PTM visits in Tambakharjo District were ownership of medical equipment (OR=0.332; 95%CI. 0.130-0.845), lack of knowledge about hypertension (OR= 2.300; 95%CI. 0.948-5.579), age ≤45 years (OR=2.53; 95%CI. 1.087-5.393), male gender (OR=6.042; 95%CI=1.677-21.778). The results of this study only describe individual factors. Further studies on psychological factors and the social environment are necessary.